Effect of Nuclear Stiffness on Cell Mechanics and Migration of Human Breast Cancer Cells - Fischer, Tony; Hayn, Alexander; Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2020)
The migration and invasion of cancer cells through 3D confined extracellular matrices is coupled to cell mechanics and matrix mechanics. Cell mechanics is mainly determined by mechanics of the largest organelle in the cell, the nucleus, and the cytoskeletal architecture. Hence, cytoskeletal and nuclear mechanics are major contributors to cell mechanics. Among other factors, steric hindrances of the matrix confinement are supposed to affect nuclear mechanics and thus also influence cell mechanics. Therefore, we propose that the percentage of invasive cells and their invasion depths into loose and dense 3D extracellular matrices is regulated by both nuclear and cytoskeletal mechanics. In order to investigate the effect of both nuclear and cytoskeletal mechanics on the overall cell mechanics, we firstly altered nuclear mechanics by the chromatin de-condensing reagent Trichostatin A (TSA) and secondly altered cytoskeletal mechanics by addition of actin polymerization inhibitor Latrunculin A and the myosin inhibitor Blebbistatin. In fact, we found that TSA-treated MDA-MB-231 human breast cancer cells increased their invasion depth in dense 3D extracellular matrices, whereas the invasion depths in loose matrices were decreased. Similarly, the invasion depths of TSA-treated MCF-7 human breast cancer cells in dense matrices were significantly increased compared to loose matrices, where the invasion depths were decreased. These results are also valid in the presence of a matrix-metalloproteinase inhibitor GM6001. Using AFM, we found that the nuclear stiffnesses of both MDA-MB-231 and MCF-7 cells were pronouncedly higher than their cytoskeleton, whereas the nuclear stiffness of human mammary epithelial cells was decreased compared to their cytoskeleton. TSA treatment reduced cytoskeletal and nuclear stiffness of MCF-7 cells, as expected. However, a softening of the nucleus by TSA treatment may induce a stiffening of the cytoskeleton of MDA-MB-231 cells and subsequently an apparent stiffening of the nucleus. Inhibiting actin polymerization using Latrunculin A revealed a softer nucleus of MDA-MB-231 cells under TSA treatment. This indicates that actin-dependent cytoskeletal stiffness seems to be influenced by the TSA-induced nuclear stiffness changes. Finally, combined treatment with TSA and Latrunculin A further justifies the hypothesis of apparent nuclear stiffening, indicating that cytoskeletal mechanics seem to be regulated by nuclear mechanics.